Adopción de una guía para el manejo de pacientes oncológicos que asisten a consulta odontológica general, en las clínicas de la Universidad Antonio Nariño. - Lozano Oviedo, Erika Viviana; Lugo Rodríguez, Eva Melissa; Montoya Cardona, Diana Briggithe (Universidad Antonio Nariño, 2021)
Lack of knowledge about oral cancer in the common population has been reported in previous studies as a significant factor delaying the referral and treatment of oral cancer. Also, a deficiency in the knowledge of this disease in doctors and dentists would also contribute to the delay in the treatment of patients who suffer from it. In this way, the need to know your diagnosis within the basic knowledge of the general dentist is highlighted. This research stems from the need to have at the Antonio Nariño University and in Colombia an updated guide that indicates how comprehensive care should be before, during and after cancer treatment, whether radio or chemotherapy.